Guidelines for the sustainable development of the agricultural sector in Colombia - Jairo Vásquez (GEON Journal (Management, Organizations and Business), 2015)
In the XXI century due to technological development have presented social, demographic and economic changes, and in an attempt to ensure that changes affecting humanity are to improve, without damaging the environment, promoting sustainable development, which aims in the preservation, management, and appropriate use of natural resources, ecosystems and livability. Sustainable development is a relatively new concept, so it is necessary to inquire by what it really means and how to apply, therefore, primarily an exploration literature in which the various points made evidencing view and elements that enable comprehension and appropriation of the concept are established; above, allows the determination of the basic guidelines for sustainable development aimed at showing justification and purpose to achieve a common understanding on this issue, structured basic guidelines for businesses of the agricultural sector to work with environmentally responsible practices, protecting biodiversity and achieving sustainability.
Keywords: Sustainable Delevopment; Biodiversity; Resources and agricultural sectors